Lockr: Social Access Control for Web 2.0 - Tootoonchian, Amin; Gollu, Kiran K.; Saroiu, Stefan; Ganjali, Yashar; Wolman, Alec (Proceedings of the First ACM SIGCOMM Workshop on Online Social Networks (WOSN), 2008)
Sharing personal content online is surprisingly hard despite the recent emergence of a huge number of content sharing systems and sites. These systems suffer from several drawbacks: they each have a different way of providing access control which cannot be used with other systems; moving to a new system is a lengthy process and requires registration and invitation of all one’s friends to the new system; and the rules for access control are complicated and become more so as our networks of online friends grow. In this paper, we present Lockr – an access control scheme based on social relationships that makes sharing personal content easy. Lockr separates social networking information from the content sharing mechanisms, thereby eliminating the need for users to maintain many site-speciﬁc copies of their social networks. We describe Lockr’s design, security properties, and limitations. We also present how we integrated Lockrwith two popular systems for sharing content online – BitTorrent and Flickr.